2016
DOI: 10.1016/j.jmb.2016.01.029
|View full text |Cite
|
Sign up to set email alerts
|

CryptoSite: Expanding the Druggable Proteome by Characterization and Prediction of Cryptic Binding Sites

Abstract: Many proteins have small molecule-binding pockets that are not easily detectable in the ligand-free structures. These cryptic sites require a conformational change to become apparent; a cryptic site can therefore be defined as a site that forms a pocket in a holo structure, but not in the apo structure. Because many proteins appear to lack druggable pockets, understanding and accurately identifying cryptic sites could expand the set of drug targets. Previously, cryptic sites were identified experimentally by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
293
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(319 citation statements)
references
References 65 publications
7
293
0
1
Order By: Relevance
“…the thermal shift assay) (102), NMR-based fragment screens (103), competitive binding screens when a weak ligand is available (69), and affinity-based selection are all popular techniques (104). Other techniques to identify cryptic binding sites may also identify novel pockets on protein surfaces that could be targeted by degradation technologies (105, 106). …”
Section: Discussionmentioning
confidence: 99%
“…the thermal shift assay) (102), NMR-based fragment screens (103), competitive binding screens when a weak ligand is available (69), and affinity-based selection are all popular techniques (104). Other techniques to identify cryptic binding sites may also identify novel pockets on protein surfaces that could be targeted by degradation technologies (105, 106). …”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate how conformational changes impact druggability, we applied our druggability prediction models to two systems containing cryptic binding sites. [38][39][40] It has been reported that appropriately sized pockets of the biologically relevant drug targets are necessary for the strong binding of drug-sized ligands. 41,42 For the target proteins that are considered tractable but less-druggable, it is of interest to identify their cryptic sites and to exploit those sites to boost the druggability of the drug targets.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying these cryptic sites could offer new druggable sites on established drug targets, provide a means to inhibit proteins that are currently considered undruggable, or enable the enhancement of desirable activities. 3,4 Raltegravir, for example, is a first-line treatment for HIV infection 5 that inhibits HIV integrase by binding a cryptic pocket. However, the population of a given excited state is often too low to detect experimentally unless a binding partner that stabilizes it is present.…”
Section: Introductionmentioning
confidence: 99%